Recent catalytic advances in the production of adipic acid and its esters from bio-based C6 molecules and carbon dioxide - Dinesh Kumar Mishra; Cong Chien Truong; Yeongin Jo; Young-Woong Suh (Green Chemistry Letters and Reviews)
Adipic acid (AA), used in the manufacture of nylon-6,6, polyurethane, and plasticizers, is derived from multi-stage processing of petrochemical resources, posing serious harms to human being and environment. Owing to the recent mounting concern over carbon footprint, the establishment of AA and its esters from renewable bio-based C6 molecules and carbon dioxide (CO2) has come into the limelight. Here, we review the eco-friendly valorization of renewable bio-based C6 molecules, such as 5-hydroxymethylfurfural derivatives (e.g. 2,5-furandicarboxylic acid, 2,5-tetrahydrofuran dicarboxylic acid, and 1,6-hexanediol), sugar acid derivatives (i.e. d-glucaric acid, d-glucarate-6,3-lactone esters, glucarodilactone, mucic acid, and muconic acid), and CO2 into AA and its esters through a wide assortment of homogeneous and heterogeneous catalysis. The aspects of catalyst evaluation, operating conditions, and reaction mechanisms are comprehensively discussed. Last but not least, specific advices for developing novel catalytic systems and future opportunities in the sustainable production of AA and its esters are also provided.